Racism in environmental communication about plastic pollution - Elander, Angelina (2020)
This thesis contributes to the knowledge formation of how environmental racism is covertly transformed in environmental communication about plastic pollution and how that affects socioecological relations in Kwazulu Natal, South Africa. Through analysis rhetorical and narrative strategies of the communication by the NGO Durbanites Against Plastic Pollution and by observing the Durbanites it has been revealed how aversive racism is transformed within the context of plastic pollution. The findings suggest that the longterm racist conditioning of apartheid and restructuration into the post-apartheid society has created a hegemonic culture of silence that prevents open discussions about social and environmental problematics related to racism. To avoid risking conflict these problems are covertly addressed within the safe premises of environmental communication about plastic pollution through symbolism and tropes in sub narratives about stereotyping, racial melancholia, corruption and child homicide. This thesis illustrates how racial tensions can amplify in the context of an environmental crisis and how environmental issues are utilized to give agency to preexisting conflicts and frame issues of the Afrikaner community. The thesis concludes that white supremacy is an environmentally dysfunctional ideology and that racism needs to be discussed in the open to reduce the taboo and prevent racist ideologies to distract the development of sustainable socioecological relations that are necessary to mitigate plastic pollution and environmental degradation.